Analisa faktor yang berpengaruh terhadap permintaan tepung terigu oleh industri kecil berbahan baku - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT This research was conducted to identify all influencing factors of wheat flour demand of industries, which used wheat flour as main raw material. Samples of this research were five noodle industries and ten sweet cake industries in Yogyakara municipality. Dependent variable influencing to wheat flour demand of small scale industries were price of wheat flour, price of substitutes (rice flour and tapioca starc101 industry's income, and governmental regulation for wheat flour distribution. A double regression method was used to determine the roles of each dependent variable. Result of data analysis showed, that the wheat flour demand was influenced by five factors in following equation: Qt = 0.027 p f 0.090 p 11,0.124 prp0.028 yb0.427 W.926 E-0,03604-u If the price of wheat flour (Pt) increased at 1%, the demand of it (Qt) decreased at 0.09%. The increase in price of rice flour (Ptb) 1% caused the increase in demand of wheat flour (Qt) for 0.124%